ESQ dan Kebutuhan Spiritualitas Civitas Akademik - Ilham Hamid (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2014)
The nature of human beings are religious (homoreligious) and human nature are spiritual beings who are always working to stay in a healthy mental, in order to live happily and unseen. It has the potential of perfect spiritual intelligence to achieve "spiritual wellness", that is true happiness of life as a form of divine gift. For that counseling services as a form of interpersonal relationship should hold on religious values in helping, directing, and guiding individuals to develop spiritual intelligence to achieve a meaningful life and happiness intact and unified. Because of religious values are fundamental, absolute and universal.